Effects of different environmental stresses on seed germination - Souza, G. M.; Cardoso, VJM (Ista, 2000)
In this paper, the hypothesis was that different environmental stresses may show similar responses in a biological system, as exemplified by the kinetic of germination of Eucalyptus grandis W. Hill ex Maiden seeds. It was observed that the kinetic of germination depends on environmental factors, and different treatments induced similar germination responses. The treatments with PEG 6000 and NaCl suggest that germination depends on solute used, since NaCl exhibit both ionic and osmotic effects. The analysis of the results showed that different external disturbances may lead, perhaps through different physiological ways, to similar responses related to the germination process.